One step synthesis of ultrafine PHF@AuNPs nanocomposite and its application in NIR triggered photodynamic therapy - Wenhao Li; Bohao Ruan; Xinyi Chen; Feng Zhou; Xiaoyi Sun; Yuanyuan Lv (PLoS ONE, 2025)
Photodynamic therapy (PDT) is a rapid advancing treatment for cancer therapy. The main challenges in PDT include poor absorption in the “tissue optical window” and aggregation tendency of photosensitizers (PS) such as fullerene in aqueous solutions. Herein, we developed a potent nano PS: fullerene hybrid gold nanoparticles (AuNPs) composites which were ultrafine and well-dispersed with a absorption in near infrared (NIR) region. The composites could be facilely prepared by mixing the reducing and capping agent polyhydroxyl fullerene (2 mg/mL) with HAuCl 4 (2.425 mM) at equal volume for 2 h. The obtained composites were negatively charged (−26.3 mv) with the particle size of 14.3 nm. A thin layer of fullerene (~1.6 nm) was coated on the AuNPs core. AuNPs in the composites acted as the light collector, absorbing the NIR light and transferring electrons or energy to the fullerene. Consequently, the composites can be efficiently internalized by tumor cells and activated to produce reactive oxygen species (ROS) intracellularly by 808 nm laser. Enhanced PDT efficacy was observed with the IC 50 value (50 μg/mL) of the light-activated cytotoxicity and a negligible dark toxicity in vitro . This research provides new insights and methods for developing NIR light-triggered fullerene@AuNPs in PDT.